EMASJID, APLIKASI CHATBOT ISLAMI DENGAN METODE RAG (RETRIEVAL-AUGMENTED GENERATION) - Fathoni, Kholid; Sudaryanto, Aris; Syarif, Iwan; Darmawan, Zakha Maisat Eka; Yunanto, Andhik Ampuh; Prasetyo; Aji , Rendra Suprobo; Fauzy, Aryazaky Iman; Hakkun, Rizky Yuniar (Universitas Islam Malang, 2025)
The development of a religious chatbot is crucial for fostering good understanding and mitigating potential social conflicts arising from religious misunderstandings. This study introduces the Intelligent Religious Assistant ChatBot, developed using the Retrieval-Augmented Generation (RAG) method within a Large Language Model (LLM). RAG combines information retrieval from authoritative sources integrated into a database with text generation to produce user-specific answers. The application has been fully developed and performance-tested, demonstrating its capability to provide accurate and contextually appropriate answers based on authoritative Islamic references endorsed by major Indonesian Islamic organizations, including Nahdlatul Ulama, Muhammadiyah, and the Indonesian Ulema Council (MUI).